Review : determinación de los parámetros cinéticos del bagazo de caña utilizando análisis termogravimétrico (TGA) (2020)
A theorical review of the projects that determined the kinetic constants of sugar cane bagasse made in Universidad De Los Andes, checking the thermogravimetry, the kinetics of combustion and the analytical methods used to determine the activation energy (E) and the frequency constant (A).